Association of neighbourhood deprivation with risks of major amputation and death following lower limb revascularisation. (August 2020) - Heikkilä, Katriina; Loftus, Ian M.; Waton, Sam; Johal, Amundeep S.; Boyle, Jonathan R.; Cromwell, David A.
Abstract: Background and aims: Individual-level socioeconomic deprivation is associated with an increased risk of adverse patient outcomes following cardiovascular disease interventions, but the role of area-level socioeconomic circumstances as a predictor for treatment outcomes is unclear. We have examined the association of neighbourhood socioeconomic deprivation with risks of major lower limb amputation and death following surgical and endovascular lower limb revascularisation due to peripheral artery disease (PAD). Methods: Patients aged 50+ years who underwent surgical or endovascular lower limb revascularisation for PAD were identified from Hospital Episode Statistics, a nationwide hospital data warehouse in England. Major amputations and deaths within a year of revascularisation were ascertained from HES and national mortality register, respectively. Index of Multiple Deprivation (IMD) was used to measure neighbourhood deprivation. Flexible parametric competing risks models were used to estimate sub-distribution hazard ratios (SHRs) for amputation and death. Results: In all, 65, 806 patients underwent endovascular and 20, 072 underwent surgical revascularisation. The covariate-adjusted 1-year risk of major amputation was higher among patients from the most deprived compared to least deprived neighbourhoods following endovascular revascularisation (SHR: 1.24, 95% confidence interval, CI:1.10 to 1.38) and surgical revascularisation (SHR:1.28, 95% CI: 1.09 to 1.51). The risk of death was higher in most deprived compared to the least deprived neighbourhoods following both procedures. Conclusions: We found a consistent association between neighbourhood deprivation and amputation and death outcomes following lower limb revascularisation for PAD. These findings suggest there may be opportunities for targeted interventions to improve care of PAD patients in deprived neighbourhoods. Graphical abstract: Image 1 Highlights: The extent to which socioeconomic deprivation impacts on treatment outcomes in peripheral artery disease is unclear. We examined the risks of major amputation and death following lower limb revascularisation for peripheral artery disease. Nationwide data suggest that neighbourhood deprivation is associated with a high risk of amputation after revascularisation.